An Implicit Plan Still Overrides an Explicit Strategy During Visuomotor Adaptation Following Repetitive Transcranial Magnetic Stimulation of the Cerebellum. (30th June 2020) - Nevels, Michael; Voets, Sarah H. E. M.; Panouilleres, Muriel T. N.; Jenkinson, Ned
Abstract: Motor adaptation is a process by which the brain gradually reduces error induced by a predictable change in the environment, e.g., pointing while wearing prism glasses. It is thought to occur via largely implicit processes, though explicit strategies are also thought to contribute. Research suggests a role of the cerebellum in the implicit aspects of motor adaptation. Using non-invasive brain stimulation, we sought to investigate the involvement of the cerebellum in implicit motor adaptation in healthy participants. Inhibition of the cerebellum was attained through repetitive transcranial magnetic stimulation (rTMS), after which participants performed a visuomotor-rotation task while using an explicit strategy. Adaptation and aftereffects of the TMS group showed no difference in behaviour compared to a Sham stimulation group, therefore this study did not provide any further evidence of a specific role of the cerebellum in implicit motor adaptation. However, our behavioral findings replicate those in the seminal study by Mazzoni and Krakauer (2006 ).